Kinerja dan Kesejahteraan Guru di Pelosok Indonesia - Siregar, Diana Riski Sapitri; Zahruddin, Zahruddin; Maftuhah, Maftuhah (Lembaga Yasin AlSys, 2022)
Teacher performance is a condition that shows the ability of teachers to carry out their duties and obligations during learning activities at school and can provide encouragement and influence to students so that learning objectives can be achieved and run well and as expected, which is shown in performance, actions. , and work performance. Welfare is important for teachers, because adequate welfare can improve the quality of the teaching and learning process, performance and professional abilities. The purpose of this study is to describe the performance and welfare of teachers in remote parts of Indonesia. The method used in this study is a qualitative approach with a literature study method that collects data from documentation of books, articles, memos, newspapers and others. The results of this study indicate that in an effort to reward teachers in remote areas or special areas, the government has issued Government Regulation No. 41 of 2009 concerning Professional Allowances for Teachers and Lecturers, Special Allowances for Teachers and Lecturers, and Honorary Professor Allowances. However, until now there are teachers who receive wages below the minimum salary set by the government. In addition, supporting factors for teacher performance such as infrastructure in remote schools still need a helping hand from the government. Therefore, it is time for Indonesia to develop into a quality nation, a nation capable of managing its human resources effectively.